Improving the catchment scale wetland modeling using remotely sensed data. (December 2019) - Lee, S.; Yeo, I.-Y.; Lang, M.W.; McCarty, G.W.; Sadeghi, A.M.; Sharifi, A.; Jin, H.; Liu, Y.
Abstract: This study presents an integrated wetland-watershed modeling approach that capitalizes on inundation maps and geospatial data to improve spatial prediction of wetland inundation and assess its prediction uncertainty. We outline problems commonly arising from data preparation and parameterization used to simulate wetlands within a (semi-) distributed watershed model. We demonstrate how wetland inundation can be better captured by the wetland parameters developed from remotely sensed data. We then emphasize assessing model prediction using inundation maps derived from remotely sensed data. This integrated modeling approach is tested using the Soil and Water Assessment Tool (SWAT) with an improved riparian wetlands (RWs) extension, for an agricultural watershed in the Mid-Atlantic Coastal Plain, US. This study illustrates how spatially distributed information is necessary to predict inundation of wetlands and hydrologic function at the local landscape scale, where monitoring and conservation decision making take place. Highlights: An integrated modeling is presented to improve wetland inundation prediction. Inundation maps are used for wetland parameterizations. Streamflow is not rarely affected by different wetland parameterizations. Inundation simulation is best achieved with the parameters from inundation maps.